Asuhan Keperawatan Pada Ny. D Dengan Anemia Pada Kehamilan: Laporan Kasus Di Ruang Nusa Indah RSUD Dr. Soeselo, Kabupaten Tegal - Nadila Azkiya Sofiyani; Tati Karyawati; Siti Fatimah (STIKES Columbia Asia Medan, 2025)
Anemia in pregnancy is a major health problem that increases maternal and fetal morbidity and mortality, thus requiring prompt and appropriate management. This study aimed to describe nursing care for Mrs. D, a 19-year-old primigravida with anemia in the Nusa Indah Ward of RSUD dr. Soeselo, Tegal Regency. The method used was a case report with data collected through interviews, direct observation, and medical record review during hospitalization from January 13–15, 2025. Assessment results showed a hemoglobin level of 6.5 g/dL with clinical signs of pallor, cold extremities, tachycardia, and complaints of dizziness and weakness. The nursing diagnoses established were ineffective peripheral perfusion and risk for nutritional deficit. Interventions included monitoring vital signs, providing nutritional education, administering iron and folic acid supplements, and collaborating on blood transfusion. Evaluation indicated both subjective and objective improvement, and the nursing problems were resolved. In conclusion, comprehensive and collaborative nursing care contributed to the improvement of the patient’s condition with pregnancy-related anemia.